Gastroprotective Properties of Karanjin from Karanja (Pongamia pinnata) Seeds; Role as Antioxidant and H+, K+-ATPase Inhibitor. (13th March 2011) - Vismaya,; Belagihally, Srikanta M.; Rajashekhar, Sindhu; Jayaram, Vinay B.; Dharmesh, Shylaja M.; Thirumakudalu, Sindhu Kanya C.
Abstract : Plant extracts are the most attractive sources of newer drugs and have been shown to produce promising results for the treatment of gastric ulcers. Karanjin, a furano-flavonoid has been evaluated for anti-ulcerogenic property by employing adult male albino rats. Karanjin (>95% pure) was administered to these rats in two different concentrations, that is, 10 and 20 mg kg −1 b.w. Ulcers were induced in the experimental animals by swim and ethanol stress. Serum, stomach and liver-tissue homogenates were assessed for biochemical parameters. Karanjin inhibited 50 and 74% of ulcers induced by swim stress at 10 and 20 mg kg −1 b.w., respectively. Gastric mucin was protected up to 85% in case of swim stress, whereas only 47% mucin recovery was seen in ethanol stress induced ulcers. H +, K + -ATPase activity, which was increased 2-fold in ulcer conditions, was normalized by Karanjin in both swim/ethanol stress-induced ulcer models. Karanjin could inhibit oxidative stress as evidenced by the normalization of lipid peroxidation and antioxidant enzyme (i.e., catalase, peroxidase and superoxide dismutase) levels. Karanjin at concentrations of 20 mg kg −1 b.w., when administered orally for 14 days, did not indicate any lethal effects. There were no significant differences in total protein, serum glutamate pyruvate transaminase, serum glutamate oxaloacetate transaminase and alkaline phosphatase between normal and Karanjin-treated rats indicating no adverse effect on major organs. During treatment schedule, animals remained as healthy as control animals with normal food and water intake and body weight gain.